Ethical Aspects of Prodromal Synucleinopathy Prognostic Counseling - Stefani, Ambra; Mozersky, Jessica; Kotagal, Vikas; Högl, Birgit; Ingravallo, Francesca; Ju, Yo-El S.; Avidan, Alon; Sharp, Richard; Videnovic, Aleksandar; Schenck, Carlos H.; St Louis, Erik K. (Seminars in Neurology, 2023)
Alpha-synucleinopathies can be identified in their prodromal phase, raising several ethical issues. In this review, we first provide definitions of prodromal α-synucleinopathies and discuss the importance of distinguishing between prodromes and risk factors. Next, we discuss the implications of a diagnosis of prodromal α-synucleinopathy and considerations regarding prognostic counseling in both clinical and research settings. We review available data on patient preferences regarding disclosure as well as providers' perspectives. We examine the pros and cons of disclosing a diagnosis of prodromal α-synucleinopathy, taking into consideration the differences between clinical and research settings. Asking about willingness to know in clinical and research settings and the shared decision-making process applied to prognostic counseling is discussed. Concerning research settings, ethical aspects regarding clinical trials are addressed. Availability of direct-to-consumer technologies will likely lead to novel contexts requiring prognostic counseling, and future neuroprotective or neuromodulating treatments may require further considerations on the timing, role, and importance of prognostic counseling. Recommendations on how to address ethical gaps should be a priority for patients, medical professional societies, and research workgroups. Ethical issues must be considered as an integral part of the overall clinical and research approach to prodromal synucleinopathies.
Keywords: RBD; REM sleep behavior disorder neurodegeneration; ethics; alpha-synuclein